2022
DOI: 10.1071/cp21735
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilisation affected zinc and selenium biofortification in silage maize

Abstract: Context Biofortification of forage crops has become even more important, due to the improvement in livestock nutrition, but it has also had an indirect positive impact on the human diet. Aim This study investigated the effect of nitrogen and microelement (Zn and Se) fertilisation on yield and on the microelement composition of maize (Zea mays L.) silage. Methods Two field experiments were conducted using a two-factorial split-plot design with nitrogen fertilisation in three doses: 0, 120, 180 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It is noted that selenite and selenate are transported to the roots by the phosphate transport mechanism and sulfate transporters and channels, respectively (Gupta and Gupta, 2017). Se biofortification by arbuscular mycorrhizal fungi (AMF) on Allium cepa L. had a friendly interaction to enhance the yield and quality of bulbs (Golubkina et al, 2019). Petkovićet al (2022 reported that macroelements such as nitrogen along with Zn and Se have a positive effect on the yield of silage maize (Zea mays L.).…”
Section: Application Of Selenium and Zinc For Crop Biofortificationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that selenite and selenate are transported to the roots by the phosphate transport mechanism and sulfate transporters and channels, respectively (Gupta and Gupta, 2017). Se biofortification by arbuscular mycorrhizal fungi (AMF) on Allium cepa L. had a friendly interaction to enhance the yield and quality of bulbs (Golubkina et al, 2019). Petkovićet al (2022 reported that macroelements such as nitrogen along with Zn and Se have a positive effect on the yield of silage maize (Zea mays L.).…”
Section: Application Of Selenium and Zinc For Crop Biofortificationmentioning
confidence: 99%
“…Se biofortification by arbuscular mycorrhizal fungi (AMF) on Allium cepa L. had a friendly interaction to enhance the yield and quality of bulbs ( Golubkina et al., 2019 ). Petković et al. (2022) reported that macroelements such as nitrogen along with Zn and Se have a positive effect on the yield of silage maize ( Zea mays L.).…”
Section: Application Of Selenium and Zinc For Crop Biofortificationmentioning
confidence: 99%
“…Several studies on biofortification have reported positive effects of the combined applications of N and micronutrients (see Kaur and Singh 2022). Based on field experiments, Petković et al (2022) recommended combining N applications with Zn and Se applications for increased fodder yield and improved mineral composition. In another study, both the soil application of Se-enriched urea and foliar spray of Se significantly increased Se contents in grains of common beans (Araújo et al 2022).…”
Section: Mineral Biofortificationmentioning
confidence: 99%
“…Crop growth, phenology, and yield are also affected by genetics ( Barlow et al., 2012 ; Borreani et al., 2018 ; Gruber et al., 2018 ), environmental ( Bernardes et al., 2018 ), and management factors ( Nilahyane et al., 2020 ; Petković et al., 2022 ). For the latter, the inputs of nitrogen (N) fertiliser and water have the greatest economic and environmental impact with regards to maize production ( Petković et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Crop growth, phenology, and yield are also affected by genetics ( Barlow et al., 2012 ; Borreani et al., 2018 ; Gruber et al., 2018 ), environmental ( Bernardes et al., 2018 ), and management factors ( Nilahyane et al., 2020 ; Petković et al., 2022 ). For the latter, the inputs of nitrogen (N) fertiliser and water have the greatest economic and environmental impact with regards to maize production ( Petković et al., 2022 ). Optimal irrigation of maize crops can increase biomass partitioning to grain ( Li et al., 2020 ) and the management of irrigation and N (defined by rate and timing) can affect dry matter allocation to different parts of the plant, and, therefore, maize silage nutritive value ( Nilahyane et al., 2020 ; Zhou et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%